MANEUVERING PERFORMANCE OF A FERRY AFFECTED BY RUDDER AREA AND SPEED - Muhammad, Andi Haris; Djabbar, Muhammad Alham; Yuniarsih, Nidia (Diponegoro University, 2013)
The aim of the study is to determine the effect of rudder area and speed on a ferry ship maneuvering performance, especially during the turning circle and zigzag maneuver. Â MATLAB-simulink was used to simulate turning circle and zigzag maneuver. The simulation utilized model based on the concept of Mathematical Modelling Group (MMG) includes testing/separating components of the hull equations, propeller and rudder as well as the interaction among them (hull, propeller and rudder). The result of simulation indicated that rudder Â dimension and ship speed Â affect both turning circle and zigzag maneuver of the ferry reasonably.